Weed flora in crop rotation and winter wheat monoculture - Andrzej Woźniak; Myroslawa Soroka (Spanish Journal of Agricultural Research, 2022)
Aim of study: The goal of the study described in this manuscript was to evaluate qualitative and quantitative changes in weed flora infesting winter wheat stands grown in crop rotation and wheat monoculture.